En smal etikett - Om intrång i patent på den andra medicinska indikationen i europeisk rättspraxis och det svenska läkemedelsförmånssystemet - Düppe,Lisa (2016)
When a new medical use for a known pharmaceutical drug is discovered, it is possible to be granted a second medical use patent. Second medical use patents were previously not accepted due to the general novelty requirement for patents and the prohibition of patents on treatments by surgery or therapy and diagnostic methods. Due to the developments in EPO case law and the revision of EPC it is however today possible be granted a second medical use patent. It can however be questioned whether the requirements for establishing infringement of such patents are too difficult. This is particularly problematic when generic manufacturers use the method of skinny labelling to exclude patented indications from the product information. Since the patented and generic products are based on the same active substance, generic substitution is possible based on the active substance. Such generic substitution has occurred, and led lawsuits around Europe. Two recent judgements in the UK and the Netherlands, which specifically address the issue of patent infringement on second medical use patents and skinny labelling, reflect the legal uncertainty that this area of law is characterized by. From a Swedish perspective the issue is further complicated as a result of mandatory provisions on generic substitution. Due to these provisions inexpensive generic versions, which solely obtain marketing approval for non-patented indications, can be substituted at local pharmacies regardless of which indication the pharmaceutical drug has been prescribed for. Subsequently, since the Swedish authorities do not consider patented indications in its assessment of generic substitution, generic versions will also be end up being used for patented indications. In order to solve this issue, it is the author’s opinion that the legislator should review the regulatory framework of second medical use patents and generic substitution. A regulatory system that facilitates infringements in valid patents is not sustainable. The Swedish regulatory system with generic substitution combined with doctors’ freedom to prescribe whatever pharmaceutical drug they consider be the most suitable regardless of the patented indication, facilitates intentional as well as unintentional infringement of second medical use patents. The legal uncertainty could affect pharmaceutical companies’ will to make major and vital investments in the continued development of necessary pharmaceutical drugs.
Keywords: Immaterialrätt; Patenträtt; Skinny labelling; Läkemedelspatent